Interfacial properties of self-assembled GaN nanowires on pre-processed Al2O3(0001) surfaces. (15th November 2016) - Koukoula, T.; Kioseoglou, J.; Kehagias, Th.; Furtmayr, F.; Eickhoff, M.; Kirmse, H.; Karakostas, Th.; Komninou, Ph.
Abstract: Surface treatment of the foreign substrate is a critical factor influencing heteroepitaxial catalyst-free growth of nanowires, their crystal quality, their diameter and their areal density. To this end, catalyst-free growth of GaN nanowires on Al2 O3 (0001) by plasma-assisted molecular beam epitaxy was achieved using the following substrate surface treatments: (a) deposition of a Six Ny layer on nitridated Al2 O3 surface, and (b) deposition of Si on bare Al2 O3 surface. The nanostructure of GaN nanowires and GaN/Al2 O3 interfaces was explored by quantitative high-resolution transmission electron microscopy and related analytical methods. Spontaneous growth of GaN nanowires was realized on the amorphous Six Ny layer, while a discontinuous crystalline zone in contact with Al2 O3 was identified as partially strained AlN. Subsequently, GaN nanowires were directly grown on top of Al2 O3 among stress-free Si islands. The orientation relation of these islands with the substrate was the [112]( 1 ¯ 1 ¯ 1 )Si//[ 1 1 ¯ 00 ](0001)Al2 O3, providing the minimum lattice misfit between the two structures. Increasing the Si deposition time a higher density of Si islands was realized, leading to non-coalesced nanowires of lower density and better structural quality. Hence, the presence of Si islands induced a mask-like effect on the nucleation of GaN nanowires that can be exploited for a controlled catalyst-free growth of nanowires.